Clinical characteristics and needle aspiration management of Bacillus Calmette-Guérin lymphadenitis in children - Suliman, Omer M. (Saudi Med J, 2015)
OBJECTIVES: To describe characteristics of children developing Bacillus Calmette-Guérin (BCG) lymphadenitis, and to evaluate needle aspiration treatment. METHODS: Children developing BCG lymphadenitis following BCG vaccination in Al-Rass General Hospital, Al-Rass, Saudi Arabia were prospectively studied from October 2008 to September 2013. Non-suppurative BCG lymphadenitis was conservatively managed, while suppurative lymphadenitis was treated by needle aspiration. RESULTS: The mean (SD) age of children (n=23) was 4.1 (1.4) months, and symptoms duration was 2.08 (1.38) months. Fifteen (65.2%) children had suppurative, whereas 8 (34.8%) had non-suppurative lymphadenitis. Age, gender, birth weight, and duration of symptoms were not significantly different between children with suppurative and non-suppurative lymphadenitis (p>0.05). Children with suppurative adenitis had higher weight, and larger size of the involved lymph nodes compared with those with non-suppurative nodes (p=0.001). Most (91.3%) had axillary lesions; with a mean lymph node size of 3.2 cm. Abscesses were detected by ultrasound in 8 (80%). Non-suppurative lymphadenitis was conservatively managed, while suppurative was aspirated. The mean duration for resolution was 3.25 months. Lymph nodes aspirate were positive for acid and alcohol fast bacilli in 10 patients (66.6%), and 3 of them grew Staphylococcus aureus. CONCLUSION: Bacillus Calmette-Guérin adenitis occurs in young children, mainly as unilocular suppurative left axillary group with a mean size of 3.2 cm. Needle aspiration is safe in treatment of suppurative lymphadenitis. Mycobacteria stained positive in most of the suppurative lesions. Excision is not needed.